NORMATIVE VALUES OF STRENGTH IN ADULTS AGED 18 TO 24 YEARS (CIPEEX, 2025)
Objective: The study aims to outline normative values in Brazilians for handgrip strength of the right and left hands in adults of both sexes aged between 18 and 24 years. Material and Methods: Forty-one thousand, five hundred and ninety-one subjects were evaluated, with 23,931 women and 17,660 men, mean age 21.33 ± 1.99 years, body mass 69.38 ± 15.97 kg, and height 168.5 ± 9.2 cm, respectively. They were submitted to handgrip strength testing with the hydraulic dynamometer “Force,” provided by the company Tera Science, using secondary data supplied by the company. Results: The results show that women had 24.24 ± 5.44 kgf in the left hand and 25.99 ± 5.56 kgf in the right hand, while men had 39.68 ± 8.96 kgf in the left hand and 41.95 ± 9.29 kgf in the right hand, respectively. Conclusion: This work presented an initial contribution to normative values of handgrip strength in the Brazilian population aged between 18 and 24 years.
Keywords: Brazilian population; Strength; Dynamometry